Q: How do you solve 3x-2 47?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x

This is an expression and you do not solve an expression, but you can factor this one.X2 + 3X4X2(1 + 3X2)========

x=-.25.

If you set your equation to equal 7, then you can move 7 to the other side of the equation, and solve for x. This/these values will always result in 7. e.g. 3x2+11x+6=7 3x2+11x+6-7=7-7 3x2+11x-1=0 Factor using the quadratic formula and solve for x.

75

Related questions

3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x

This is an expression and you do not solve an expression, but you can factor this one.X2 + 3X4X2(1 + 3X2)========

x=-.25.

Set the equation equal to zero. 3x2 - x = -1 3x2 - x + 1 = 0 The equation is quadratic, but can not be factored. Use the quadratic equation.

-3x2 + 22x = 0 You start by dividing both sides by x: ∴ -3x + 22 = 0 Then rearrange to solve for x: ∴3x = 22 ∴ x = 7 + 1/3

If you mean 3x2+4x-2 = 0 then it can be solved by means of the quadratic equation formulla

x2 • (5x2 + x + 8)

If you mean 3x2-7x+x = -4 then there are no solutions because the discriminant of the quadratic equation is less than zero.

If you set your equation to equal 7, then you can move 7 to the other side of the equation, and solve for x. This/these values will always result in 7. e.g. 3x2+11x+6=7 3x2+11x+6-7=7-7 3x2+11x-1=0 Factor using the quadratic formula and solve for x.

75

you add them together 112 + 47 ------- 159

8